Improvement of Prognostic Outcome in Minimally Invasive Surgery for Stage I Epithelial Ovarian Cancer - Kohei Omatsu; Chyi-Long Lee; Kuan-Gen Huang (Gynecology and Minimally Invasive Therapy)
Objectives: Minimally invasive surgery (MIS) is a limited treatment option for early-stage ovarian cancer. The National Comprehensive Cancer Network® guidelines that salpingo-oophorectomy should be performed with every effort to keep an encapsulated mass intact during removal. We aimed to investigate whether, if tumor rupture was controlled, patients’ oncological outcomes for Stage I ovarian cancer would not be worse in MIS. An endobag was prepared and used to prevent the ovarian cancer cells from spilling into the peritoneal cavity. We report a recent 10-year clinical outcome of MIS for ovarian cancer by oncological endoscopists in gynecology. Materials and Methods: We retrospectively collected clinical data from an electric chart. Collective clinical data included age, body mass index (BMI), operative time (OT), estimated blood loss (EBL), intraoperative rupture (IR), duration of hospital stay (HS), time from the operation date to the first infusion of chemotherapy (TOFC), disease-free survival (DFS), and overall survival (OS) at 5 years. The data were statistically analyzed using EZR. Results: The median age, BMI, OT, EBL, IR, HS, TOFC, and DFS were 50 years, 23.9 kg/m2, 363 min, 100 mL, 65 (98%) patients, 7 days, 15 days, and 43.4 months, respectively. The OS was 98%. The data were consistent with those from the past 10 years, except for a tendency toward an increasing trend in the proportion of ruptured tumors during surgery. Conclusion: Tumor rupture within the prepared endobag during MIS did not affect the oncological outcomes of early-stage ovarian cancer.